Interview with Professor Samira Luitel - Subedi, Madhusudan; Khattri, Man Bahadur (Dhaulagiri Journal of Sociology and Anthropology, 2025)
Born on March 7, 1952, into an educated and socially active family, Professor Samira Luitel is a distinguished sociologist and education consultant based in Kathmandu, Nepal. With a professional career spanning over four decades, she has made substantial contributions to the fields of education, gender studies, and social inclusion. Since her retirement in 2013, she has continued her work as a freelance consultant. Professor Luitel has held significant academic and research positions, including Senior Researcher at the Research Centre for Educational Innovation and Development (CERID) and Professor at the Central Department of Sociology/Anthropology at Tribhuvan University. She has also served as a Supplemental Professor at the University of Delaware, USA. Her research focuses on the intersection of education and development, particularly concerning women, ethnic minorities, and other disadvantaged groups, employing both qualitative and quantitative methodologies. She holds a Ph.D. in International Intercultural Education from the University of Alberta, Canada. Her dissertation explored literacy and empowerment among Maithili women in Nepal. Professor Luitel has authored several publications, including books, manuals, and over two dozen research reports on gender, education, and social issues. As the first female professor of Sociology in Nepal and an active member of numerous academic and development organizations, she has significantly influenced policy-making, curriculum development, and capacity-building initiatives. Her contributions have been recognized with the Mahendra Bidhya Bhushan award for academic excellence. Professor Luitel continues to impact Nepal’s education and social development sectors through research, teaching, and advocacy. This interview was conducted in March 2025 by Professor Madhusudan Subedi and Dr. Man Bahadur Khatri, and the excerpts are presented in the order in which the questions were asked.